Exploring the development of library makerspaces in China. Issue 2 (21st May 2018) - Li, Ming; Fan, Weiguo; Luo, Xiaolan
Abstract : Purpose: In response to the government's decision to make "entrepreneurship and innovation for all" a national strategy in its 2015 annual work report, Chinese professionals in the library field have expressed a growing interest in makerspaces. This study aims to provide an overview of their current research studies and attempts in constructing makerspaces. Design/methodology/approach: The authors aggregated research materials on library makerspaces in China from two sources: journal articles from the China National Knowledge Infrastructure Database and online news reports from the search engine Baidu.com. Content analysis was used to extract information regarding visions and perceived values, service models and technology adoption. Findings: While a growing number of Chinese academic publications are concerned with library makerspaces, the existing research focuses on foreign cases and offers few empirical studies on domestic application scenarios. Libraries and researchers in China hold a positive and supportive attitude toward makerspaces. 3D printing is the most frequently mentioned technology, and free-to-use, promoting communication and realization of ideas and dreams are the most emphasized values. Libraries should highlight their own unique advantages and tap into their resources and services in mutually beneficial collaborations with other types of makerspaces. Research limitations/implications: First, the results of this study cannot fully summarize the development status of makerspaces in Chinese libraries. Second, the research materials used in this study may be biased, especially the news reports. Practical implications: This paper presents a semantic, visualized analysis of aggregated online news articles and journal articles on library makerspaces in China in an attempt to summarize their characteristics and guiding values, validate the advantages of library makerspaces and give suggestions on improving their service models. Social implications: This paper introduces the development trend of makerspace in Chinese libraries, so that researchers at home and abroad can learn more about the development of Chinese library. Originality/value: This study comprehensively overviews the development of library makerspaces in China. The results provide suggestions to improve maker services in library.